2016
DOI: 10.4172/2572-0805.1000104
|View full text |Cite
|
Sign up to set email alerts
|

Participation in PLHIV Support Groups: Does it Enhance Behavioural Outcomes?

Abstract: The role of antiretroviral therapy (ART) in HIV prevention has generated hope for an AIDS-free generation but also interest in behavioural outcomes of people living with HIV (PLHIV). This is from the knowledge that the benefits of ART in terms of enhancing PLHIV health outcomes and preventing HIV transmission depend on PLHIV's behaviours including sexual risk, disclosure, treatment adherence and retention. The purpose of this study was to examine whether PLHIV in Nigeria who participate in support group activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Data from a study carried out in Nigeria by Simpson discovered that PLWH who participated in support group activities significantly experienced less stigma than those who did not belong to support groups. 21 Turan et al also reported that women who had not linked to HIV care after testing positive at first antenatal care visit had higher levels of depression and internalized stigma compared to women who were linked to care, therefore having less benefit for both mental and physical health. 22…”
Section: Discussionmentioning
confidence: 99%
“…Data from a study carried out in Nigeria by Simpson discovered that PLWH who participated in support group activities significantly experienced less stigma than those who did not belong to support groups. 21 Turan et al also reported that women who had not linked to HIV care after testing positive at first antenatal care visit had higher levels of depression and internalized stigma compared to women who were linked to care, therefore having less benefit for both mental and physical health. 22…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of internalized stigma was lower among the members of self-help groups than non-members. Internalized stigma can be mitigated by a self-help group [ 54 ]. The members do not feel alone, which reduces their internalized stigma [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV-positive individuals. According to a study conducted by Simpson in Nigeria, HIVpositive individuals who participated in community group activities were not subject to discrimination and were readily accepted(Carlos et al, 2015;Tumwikirize & Mokoboto- Zwane, 2016). People with excellent knowledge tend not to harbour concerns or misconceptions about HIV-positive individuals.…”
mentioning
confidence: 99%